Psychometric evaluation of the UCLA PTSD Reaction Index (PTSD RI-5) in a Turkish Clinical sample of trauma-exposed children - Rana Selin Kucukardali; Beyza Nur Karal; Alan M. Steinberg; Abdurrahman Cahid Orengul (European Journal of Psychotraumatology)
Objective: Trauma victimization is common among children, however, a significant proportion of trauma victims go unrecognized unless they are thoroughly assessed, even in child psychiatry clinics. The aim of this study was to evaluate the psychometric properties and diagnostic accuracy of the Turkish version of the UCLA PTSD Reaction Index for DSM-5 (PTSD RI-5) in a clinical sample of trauma-exposed children and adolescents.Method: A total of 208 children and adolescents admitted to the child psychiatry clinic, each of whom had a history of at least one traumatic event, were evaluated with the PTSD RI-5 to investigate trauma history and PTSD symptoms. All participants also completed the Revised Child Anxiety and Depression Scale (RCADS) and 64 participants were assessed with a semi-structured diagnostic interview for PTSD and depression.Results: Internal consistency for the total scale was high (Cronbach’s α = 0.91) and the confirmatory factor analysis (CFA) supported the four-factor structure of the PTSD RI-5 (CFI =  0.915, TLI = 0.902, RMSEA =0.062). ROC analysis showed strong diagnostic accuracy (AUC = 0.94).Conclusion: The Turkish version of the PTSD RI-5 may a reliable and valid tool for diagnosing PTSD in clinical samples and may improve diagnosis and treatment outcomes by identifying unrecognized trauma-related symptoms.